2017
DOI: 10.3892/mmr.2017.7875
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5 promotes cell proliferation and invasion in hepatocellular carcinoma by targeting E2F1

Abstract: Sirtuin 5 (SIRT5) is a member of the NAD+‑dependent class III protein deacetylases. Although it is known that SIRT5 deacetylates and activates urate oxidase in the liver mitochondria of mice, the mechanism of SIRT5 in the proliferation of hepatocellular carcinoma (HCC) remains to be fully elucidated. The present study investigated the expression and functional significance of SIRT5 in HCC, and examined the relevant mechanism. SIRT5 was found to be upregulated in HCC tissues and cell lines, and the higher expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 25 publications
6
64
0
Order By: Relevance
“…SIRT5 contributes to cell invasion in HCC by targeting E2F1 [65]. Additionally, targeting SIRT5 enables miR-299-3p to inhibit the migration and invasion of HCC cells [69].…”
Section: Sirtuins and Tumor Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT5 contributes to cell invasion in HCC by targeting E2F1 [65]. Additionally, targeting SIRT5 enables miR-299-3p to inhibit the migration and invasion of HCC cells [69].…”
Section: Sirtuins and Tumor Metastasismentioning
confidence: 99%
“…Only a limited amount of research has been conducted on SIRT5 in tumorigenesis. Several recent studies have shown that SIRT5 may play a tumor-promoting role in multiple types of cancer, such as HCC [65], colon cancer [63], human osteosarcoma [63] and breast cancer [149]. Moreover, the SIRT5 gene frequently shows an increase in duplication in specific cancer types, including uterine cancer, breast cancer, cutaneous and uveal melanomas, lung cancer, and lymphoma [150].…”
Section: Sirtuins In Tumorigenesismentioning
confidence: 99%
“…Among the TFs targeted by NEIL3, E2F1 represents a key link in the cell cycle regulation network, and its aberrant expression participates in HCC occurrence and development, which also predicts the unfavorable patient prognosis [42]. As reported, E2F1, which is tightly linked to cell division cycle associated 5 (CDCA5), Sirtuin 5 (SIRT5) and other important molecules, may serve as a vital anti-apoptotic factor in liver cancer due to its ability to offset c-Myc-driven apoptosis [43,44]. As suggested in previous literature, the repressive complex, which includes the component of E2F4, is relieved by CDK upon reentry into the cell cycle; thereafter, E2F1-Sp1, which is in the form of complex E2F1-NF-Y, can be recruited to the promoter [45].…”
Section: Discussionmentioning
confidence: 90%
“…SIRT5 functions both as a lysine acetyltransferase, and as a desuccinylase, demalonylase, or deglutarylase [26][27][28]. Although several reports have indicated that SIRT5 can act as an oncogene in different cancers [29][30][31][32], SIRT5 downregulation has also been associated with poor prognosis in glioblastoma patients [33].…”
Section: Discussionmentioning
confidence: 99%